Legal Perspectives on Healthcare Inequality in Indonesia - Novita Listyaningrum,; Sukadi, Sukadi; Lubis, Junaidi (KARSA Journal of Social and Islamic Culture, 2025)
Indonesia faces significant challenges in ensuring equitable health rights fulfillment despite having comprehensive health legislation, with persistent disparities in healthcare access across geographical and socioeconomic dimensions raising questions about the effectiveness of health rights implementation within the international human rights law framework. This research aims to analyze the implementation of health rights in Indonesia within the framework of international human rights law, evaluate the conformity of Indonesian health policies with international human rights standards, identify legal and policy factors contributing to healthcare access disparities, and assess the effectiveness of health regulation implementation in ensuring citizens’ health rights fulfillment. The study employs normative-empirical methods with a policy analysis approach. Research findings demonstrate that despite Indonesia’s comprehensive legal foundation from constitutional to technical, operational regulations, healthcare access disparities remain a complex structural challenge. The evaluation of AAAQ principles (Availability, Accessibility, Acceptability, and Quality) reveals significant geographical and socioeconomic inequality, particularly between urban-rural areas and western-eastern Indonesian regions. The effectiveness of health regulation implementation shows a paradox between firm normative commitments and diverse practical realities, with challenges including coordination complexity across government levels, limited healthcare human resources, and unequal health facility distribution. This research recommends human rights-based health policy reforms that integrate Pancasila values to create a more inclusive, equitable, and sustainable healthcare system that achieves health justice in Indonesia.